(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Herbal extracts are often used by the folk medicinal practitioners, rural peoples of Bangladesh for the treatments of various ailments for the primary health care. Now-a-days its uses are going more frequent with an established scientific literature. Low cost nutritive wafer biscuits made of ayurvedic or herbal extracts such as shatavari, ashwagandha and yastimadhu powder was developed and evaluated for its chemical composition for nutritive parameters. Brief microbiological studies were also planned to evaluate the shelf life and safety of the product. Finally a sensory evaluation was conducted to ascertain its overall acceptability amongst the population. It was shown that newly developed wafer biscuits were rich in carbohydrate (65%), energy and fat (24% fat). The results indicate that newly formulated biscuits were surprising high in protein (8.20%), dietary fiber (1.5%) and widely accepted by the consumers mainly due to its low cost and health benefits with respect to sensory qualities, high nutritive values . The results also indicated that the newly formulated biscuits were high in self-life ranking and it was agreed that this type of initiative could more effective for growing children as well as in certain therapeutic conditions when general malaise dominates the diseases and such type of fortified foods can be industrially launched as a social business. J. Environ. Sci. & Natural Resources, 9(1): 17-21 2016